The Development of Augmented-Reality Based Guided Inquiry Teaching Material of Life Organization System - Linda Suci Triliana; Munzil Munzil; Sugiyanto Sugiyanto (Universitas Negeri Malang, 2021)
The purposes of this research and development is to produce feasible and valid teaching materials utilizing augmented reality-assisted guided inquiry learning model in the activity of identifying life organizational system for 7th grade students of Junior High School/Islamic Junior High School, as teaching material in Covid-19 Pandemic era. This research used Lee and Owens research and development model, limited to three stages, namely: analysis/assessment, design, and development. The feasibility of the teaching materials were determined from the results of the validation and user assessment. The teaching materials were developed in A6-sized printed books containing Basic Competence 3.6 materials of life organizational system from the cellular level to organismic level. The materials were presented in the forms of illustrations, videos, three-dimensional AR animations, and handouts on google drive. Based on the validity result which was conducted by material and media experts, it was discovered that the teaching materials were valid and feasible for learning with the score percentage of more than 81 percent.